Profil Keterampilan Berpikir Kreatif Mahasiswa Pendidikan Biologi Universitas Tanjungpura dalam Mengelola Sampah menjadi Produk - Titin Titin; Elsa Ferella; Ganis Sundawiyani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The purpose of this study was to determine the profile of Tanjungpura University Biology Education students' creative thinking skills in developing an ideas for waste management into products. This research is a descriptive qualitative research type. The data in this study are in the form of response data in the form of a questionnaire. The results showed that the creative thinking ability in the fluency aspect was 58.48% in the sufficient category, the flexibility aspect was 63.01% in the creative category, the originality aspect was 61.48% in the creative category, and the elaboration aspect was 66.40% in the creative category. Based on the percentage, it was found that the aspect with the highest value was the elaboration aspect and the lowest value was in the fluency aspect.